Das crônicas do relojoeiro as narrações do conselheiro: Policarpo e Aires dois intérpretes da república brasileira - Borges, Luciana Tavares (2012)
This dissertation aims to discuss the interpretation of the birth of the republic according to three works of Brazilian writer Joaquim Maria Machado de Assis (1839- 1908). Will be analyzed in two series chronicles Good Day! (May 27, 1888 and June 29, 1889) and the novel chronicles Esau and Jacob On, Polycarp, the narrator, makes objection to the idea of federalism, one of the defenses of the Republican campaign. Regarding the novel, we will stop to chapters 60-64 we show the position of Counselor Aires uncertainty about the rise of new political regime. The relationship between history and literature will allow us to discuss the nascent republic by the Brazilian Machado characters. Will Machado considered the birth of the republic as a positive? In the following pages, we present this and other issues in this work, which is premised analyze the triad Literature-History-Politics, the change of political regime in Brazil at the end of the nineteenth century.